1996
DOI: 10.1128/iai.64.11.4586-4592.1996
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of serum antibodies to a nonacylated form of lipoprotein D of Haemophilus influenzae

Abstract: Protein D, a surface-exposed 42-kDa membrane lipoprotein, is well conserved among both type b and nontypeable Haemophilus influenzae strains, and it is considered a vaccine against H. influenzae infections. Here, we report the large-scale purification of a nonacylated form of protein D (PDm) from the periplasmic space of Escherichia coli overexpressing PDm. Screening of human sera for levels of antibodies to PDm demonstrated that the immunoglobulin G (IgG) antibody level is above background levels in infants l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Different from the total antibody results, we found that protein D less frequently induced bactericidal antibody compared with vaccine candidate P6 in otitis-prone children and OMP26 again failed to generate any bactericidal effect. Our finding with protein D is consistent with a prior report by Akkoyunlu et al (1996). Those results along with other ongoing research in our laboratory is a step forward to understand the immunological differences in otitis-prone and nonotitis-prone children.…”
Section: Discussionsupporting
confidence: 92%
“…Different from the total antibody results, we found that protein D less frequently induced bactericidal antibody compared with vaccine candidate P6 in otitis-prone children and OMP26 again failed to generate any bactericidal effect. Our finding with protein D is consistent with a prior report by Akkoyunlu et al (1996). Those results along with other ongoing research in our laboratory is a step forward to understand the immunological differences in otitis-prone and nonotitis-prone children.…”
Section: Discussionsupporting
confidence: 92%
“…Firstly, regarding the overall lower values of the fluorescence readings for these antigens, the kinetics of the response to these proteins must be considered when evaluating these data. For instance, for H. influenzae Protein D, the levels of IgG are low until the age of 2 years, increasing to moderate levels at 2 to 10 years of age and finally reaching higher levels in adulthood (Akkoyunlu et al, 1996). As half of the tested population was aged b2 years, this factor may have contributed to the low levels of IgG found.…”
Section: Discussionmentioning
confidence: 98%
“…A later study (3) showed that rats immunized with LPD produced bactericidal antibody with activity against both homologous and heterologous NTHI isolates and also experienced an accelerated rate of recovery from experimental OM, thus generating interest in LPD as a vaccine candidate. Similarly, a nonacylated mutated form of LPD (PDm), expressed by and isolated from the periplasmic space of E. coli (32), was found to be more easily produced and purified than LPD (3,32) and also induced IgG and IgA in serum, which had significant bactericidal activity against both homologous and heterologous NTHI isolates (2). While neither LPD nor PDm immunization prevents the development of acute OM in rats, both result in more rapid recovery from disease, with LPD being the more efficacious (3).…”
Section: Discussionmentioning
confidence: 99%
“…After concentration, the product was stored in phosphatebuffered saline (PBS; pH 6.8)-0.5% Empigen BB at Ϫ20°C until formulated for use. Protein D (PDm) is a recombinant nonacylated form of LPD lacking three N-terminal palmitate residues, whose expression and purification has been described (2,3,32).…”
Section: Methodsmentioning
confidence: 99%